Prostate cancer epidemiology in the French West Indies and French Guyana - Sasco, Annie J.; Banydeen, Rishika; Azaloux, Hervé; Dieye, Moustapha; Le Mab, Guillaume; Foucan, Lydia; Olea, Nicolas; Salamon, Roger (European Journal of Oncology and Environmental Health, 2009)
Prostate cancer is the fifth cause of cancer death in the world today. In spite of numerous studies on the subject, its aetiology has not yet been clearly defined. Three French “départements”, the French Antilles (Guadeloupe and Martinique) and French Guyana present unique epidemiological, geographical, ethnic and environmental characteristics which can help elucidate the complex causes behind the disease. These particular traits have been highlighted by a systematic scientific literature review, followed by the synthesis of current main aetiological hypotheses relative to the Caribbean-Guyanese context. Martinique and Guadeloupe register high world age-standardised incidence rates for prostate cancer (exceeding 150 cases per 100,000 in 2002), twice those of mainland France and in constant increase for the past 20 years, now making them comparable to the highest world incidence rates recorded amongst Afro-Americans in the United States of America. In Guyana, prostate cancer is also one of the commonest cancers in 2007. Ninety percent of the Caribbean population and 66% of the French Guyanese are of African descent. In these populations, favoured hypotheses for prostate cancer concern, along with genetic and ethnic factors, diet (change towards Western eating habits) and sexual behaviour (possible infectious cause such as a role for Human Papilloma Virus). The eventual implication of occupational risk factors (agriculture) shown in previous studies, as well as environmental factors such as pesticide exposure, need also to be examined. In the Caribbean-Guyanese context, no aetiological study has yet been published, even though abstracts and theses are available. While the natural environment of these three French “départements” is widely recognised as being contaminated by the intense and excessive use of pesticides, the latter’s rôle in prostate cancer aetiology remains obscure, hence the need for a complete investigation, using reliable geographical, epidemiological and toxicological approaches. Only full cooperation between complementary scientific teams will help acquire the necessary knowledge for the comprehension of this complex health problem and then for effective prevention. Such a study is currently being planned in synergy with local (Martinique, Guadeloupe, Guyana) and Bordeaux researchers, and with the collaboration of other European scientists.